Marketing performance measurement: which way is up?. (2nd November 2004) - Ambler, Tim; Kokkinaki, Flora
The study reported in this paper explores the measurement of marketing performance across different business sectors. It concerns the measures collected, their relative importance and whether business characteristics (e.g. firm size, sector) differentiate such practices. The extent to which firms are satisfied with their current marketing measurement systems and the improvements sought also provide insights into how measurement is being used to enhance performance. Secondary data were collected through semi-structured interviews (n = 44) and a questionnaire-based survey (n = 531). Internal financial measures are, overall, regarded as more important measures of marketing performance than those from the market. Consistent with previous findings, customer and competitor orientation are positively associated with business performance, with customer orientation being the more important. Further, firm orientation influences how marketing is assessed in practice, e.g. customer-oriented firms tend to utilize customer based information more than firms less so oriented. Although the assessment of marketing performance requires consideration of the change of the main marketing asset, few firms formally assess brand equity for this purpose.